MALAWIAN MUSIC: A FRAMEWORK FOR ANALYSIS, Gerhard Kubik, assisted by Moya Aliya Malamusi, Lidiya Malamusi and Donald Kachamba, Centre for Social Research and Department for Fine and Performing Arts, Chancellor College, University of Malawi, Zomba, 1987. - Nurse, G. T. (International Library of African Music, 1996)
pages: 103
Keywords: African Music; Malawi